2012
DOI: 10.1093/nar/gks960
|View full text |Cite
|
Sign up to set email alerts
|

IUPHAR-DB: updated database content and new features

Abstract: The International Union of Basic and Clinical Pharmacology (IUPHAR) database, IUPHAR-DB (http://www.iuphar-db.org) is an open access, online database providing detailed, expert-driven annotation of the primary literature on human and rodent receptors and other drug targets, together with the substances that act on them. The present release includes information on the products of 646 genes from four major protein classes (G protein-coupled receptors, nuclear hormone receptors, voltage- and ligand-gated ion chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 28 publications
1
76
0
1
Order By: Relevance
“…To demonstrate potential suitability for profiling of receptor antagonists in a screening format, inhibition of Nluc-β2AR was measured using a panel of β2AR blockers in the presence of a fixed concentration (1 µM) ISO (Fig 1c). Rank-order potency of the antagonist panel was closely aligned with pharmacological profiling of ligand affinity at β2AR by traditional methods [16][17][18] observed for the Nluc-HaloTag® fusion with results similar to those obtained using Nluc alone (Fig. 2a).…”
Section: Nluc-gpcr Fusions Enable Time and Dose-dependent Measurementsupporting
confidence: 73%
“…To demonstrate potential suitability for profiling of receptor antagonists in a screening format, inhibition of Nluc-β2AR was measured using a panel of β2AR blockers in the presence of a fixed concentration (1 µM) ISO (Fig 1c). Rank-order potency of the antagonist panel was closely aligned with pharmacological profiling of ligand affinity at β2AR by traditional methods [16][17][18] observed for the Nluc-HaloTag® fusion with results similar to those obtained using Nluc alone (Fig. 2a).…”
Section: Nluc-gpcr Fusions Enable Time and Dose-dependent Measurementsupporting
confidence: 73%
“…To identify candidate C-peptide receptors, we used the Deductive LigandReceptor Matching Strategy developed by our laboratory to identify the receptor for the neuropeptide neuronostatin (114). We first screened three cell lines found to respond to C-peptide, including the human erythroleukemia cell line TF-1, the human embryonic kidney cell line HEK 293, and the human gastric tumor cell line KATOIII, for the expression of all known orphan GPCRs, as catalogued by IUPHAR (93). We found that 24 of the ϳ136 orphan GPCRs were expressed by TF-1, HEK 293, and KATOIII cells.…”
Section: Searching For a C-peptide Receptormentioning
confidence: 99%
“…The neuropeptide Y system, comprising neuropeptide Y (NPY), peptide YY (PYY), pancreatic polypeptide (PP) and the corresponding Y receptors (Y1, Y2, Y4, Y5 and Y6), is well known for its role in the regulation of energy homeostasis and associated processes [52,53]. NPY, PYY and PP have been classified into a family of homologous peptides because of their sequence homology and common tertiary structural motif, a hairpin fold [54].…”
Section: Y Receptorsmentioning
confidence: 99%